Metagenomic Analyses Reveal Distinct Gut Microbiota Signature for Predicting the Neoadjuvant Chemotherapy Responsiveness in Breast Cancer Patients - Li, Yuanyuan; Dong, Bingbin; Wu, Wei; Wang, Jiawei; Jin, Hao; Chen, Kangmei; Huang, Kangling; Huang, Songyin; Yao, Yandan (Frontiers in Oncology, 2022)
Background: Growing evidence supports the modulatory role of human gut microbiome on neoadjuvant chemotherapy (NAC) efﬁcacy. However, the relationships among the gut microbiome, tumor-infiltrating lymphocytes (TILs), and NAC response for breast cancer (BC) patients remain unclear. We thus proposed this preliminary study to investigate the relationship between gut microbiome and BC patients’ responses to NAC treatment as well as underlying mechanisms. Methods: Prior to receiving NAC, the fecal metagenome collected from 23 patients with invasive BC were analyzed. Patients were subsequently assigned to NAC non-effectual group and NAC effectual group based on their response to NAC. The peripheral T lymphocyte subsets counts were examined by flow cytometry methods. CellMinor analysis was employed to explore the relationship between CD4 mRNA expression and reaction of tumor cells to NAC drugs. Results: The gut microbiomes of the NAC non-effectual group showed characteristics of low diversity with low abundances, distinct metagenomic composition with decreased butyrate-producing and indolepropionic acid-producing bacteria, and increased potential pathobionts compared with NAC effectual group. The combination of Coprococcus, Dorea, and uncultured Ruminococcus sp. serves as signature bacteria for distinguishing NAC non-effectual group patients from NAC effectual group. The absolute numbers of CD4+ and CD8+ TIL inﬁltration in tumors in NAC non-effectual group was significantly lower than that in the effectual group. Similar findings were reported for the CD4+ T lymphocytes in the peripheral blood (ps < 0.05). NAC effectual-related signature bacteria were proportional to these patients’ CD4+ T lymphocytes counts in peripheral blood and tumors (ps < 0.05). The CellMinor analysis showed the CD4 mRNA expression level dramatically climbed with increased sensitivity of tumor cells to NAC drugs such as cyclophosphamide, cisplatin, and carboplatin (ps < 0.05). Conclusions: The composition of the gut microbial community differs between BC patients for whom NAC is effective to those that are treatment resistant. The modulation of the gut microbiota on host CD4+ T lymphocytes may be one critical mechanism underlying chemosensitivity and NAC pathologic response. Taken together, gut microbiota may serve as a potential biomarker for NAC response, which sheds light on novel intervention targets in the treatment of NAC non-effectual BC patients.